(untitled) (Revista NUPEART, 2023)
Dealing with the Theatre of the Oppressed makes us recognize that this is originally a decolonial method to the extent that it is not guided by precepts other than those of problematizing the issues concerning the oppressed and oppressed. I refer to the oppressions of the real world, the specific spectacle that this theater produces, the political intentions that move the practi[1]tioners, as well as the modes of transmission of artistic produc[1]tion that has popular characteristics. In this sense, this article proposes to present the method created by Augusto Boal as a recommended proposal for Brazilian basic education. It means that by being structured as a transgressive and democratic artistic method, having a recognized and appreciated presence in contemporary contexts, schools are the significant spaces to assert their potentialities.